Estimating Pedestrian Impact on Coordination of Urban Corridors. Issue 7 (July 2019) - Chowdhury, Sharmin-E-Shams; Stevanovic, Aleksandar; Mitrovic, Nikola
Pedestrian walk timings at most U.S. traffic signals are run in concurrence with relevant signal phases for vehicular traffic. This usually means that signal operations coordinated for the major street can be interrupted by a pedestrian call. Such an interruption may in practice last for a few minutes, thus causing increased delays and stops for major traffic flows. An alternative to this design is to increase the cycle length and embed pedestrian timings within the ring-barrier structure of the prevailing coordination plan. Both approaches have advantages and disadvantages. A fresh approach offered by this study is a comprehensive experimental design and holistic performance evaluation perspectives. The study examines the two abovementioned treatments of pedestrian timings for a small corridor of five intersections in Utah. The experiments have been done in a high-fidelity microsimulation environment with the Software-in-the-Loop version of the field controller (Econolite ASC/3). Findings show that either approach works well for very low traffic demands. When the traffic demand increases findings cannot be generalized as they differ for major coordinated movements versus overall network performance. While major-street traffic prefers no interruption of the coordinated operations, the overall network performance is better in the other case. This can be explained by the fact that avoiding interruptions is usually achieved at the expense of longer cycle length, which increases delay for everyone in the network.